2016
DOI: 10.1186/s12913-016-1347-0
|View full text |Cite
|
Sign up to set email alerts
|

Effort-reward imbalance and self-rated health among Gambian healthcare professionals

Abstract: Background: The effort-reward imbalance (ERI) model of work stress has been widely applied in investigating association between psychosocial factors at work and health. This study examined associations between perceived psychosocial work stress as measured by the ERI model and self-rated health (SRH) among nurses and environmental health officers (EHOs) working in secondary public healthcare facilities in the Gambia. Method: A cross-sectional study on a random sample of 287 health care professionals (201 nurse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
1
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 25 publications
2
29
1
3
Order By: Relevance
“…Our results confirm previous studies indicating that ERI might be a risk factor for health outcomes including self-rated overall health,46 low back pain47 and mental distress3 in different working populations. Self-rated health was described to be a good indicator of health status and mortality risk48 especially for women 49.…”
Section: Discussionsupporting
confidence: 91%
“…Our results confirm previous studies indicating that ERI might be a risk factor for health outcomes including self-rated overall health,46 low back pain47 and mental distress3 in different working populations. Self-rated health was described to be a good indicator of health status and mortality risk48 especially for women 49.…”
Section: Discussionsupporting
confidence: 91%
“…and Brazil (65.6%) [11,29,30]. Additionally, this rate was lower than that of the general population in previous studies [31,32], suggesting that self-rated health among healthcare workers in the current study was generally low.…”
Section: Discussioncontrasting
confidence: 68%
“…This model also proposes that this process will be reinforced by overcommitment, such that overcommitted employees will respond with more strained reactions to an effort-reward imbalance compared to less committed employees. Previous studies found that ERR and overcommitment were signi cantly associated with adverse health outcomes among healthcare workers in Gambia, Japan, and China [11,12,15,16]. Likewise, empirical studies found that ERR and overcommitment signi cantly predicted other negative outcomes, such as low job satisfaction and low work engagement [15,17,18].…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Effort-reward imbalance is an important factor causing the decline in the health status of healthcare workers [ 11 , 12 ]. Siegrist proposed the effort-reward imbalance model to explain this association.…”
Section: Introductionmentioning
confidence: 99%